2016
DOI: 10.15414/jmbfs.2016.5.6.530-533
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Method for Environmental Dna Extraction and Purification From Soil

Abstract: Large proportion of microbial population in the world is unculturable. Extraction of total DNA from soil is usually a crucial step considering to the difficulties of study the uncultivable microorganisms. Humic acid is considered as the main inhibitory agent in the environmental DNA studies. Here, we introduced a rapid and efficient method for DNA extraction and purification from soil. Yield of DNA extraction by the presented method was 130 ng/µl. Three conventional methods of DNA extraction including liquid n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Incorporating a bead-beating step prior to the freeze-thaw cycles did result in improved DNA yields (p < 0.05). This is in alignment with other studies in which these two pretreatments demonstrated more satisfactory results for DNA extraction from Cryptosporidium oocysts and other protozoa compared to solely using freeze-thaw pretreatment (Babaei et al, 2011; Hamedi et al, 2016; Mthethwa et al, 2022). However, the DNA yields from combined pretreatments were still lower than those from bead-beating alone, indicating significant DNA loss due to degradation during the freeze-thaw process.…”
Section: Resultssupporting
confidence: 90%
“…Incorporating a bead-beating step prior to the freeze-thaw cycles did result in improved DNA yields (p < 0.05). This is in alignment with other studies in which these two pretreatments demonstrated more satisfactory results for DNA extraction from Cryptosporidium oocysts and other protozoa compared to solely using freeze-thaw pretreatment (Babaei et al, 2011; Hamedi et al, 2016; Mthethwa et al, 2022). However, the DNA yields from combined pretreatments were still lower than those from bead-beating alone, indicating significant DNA loss due to degradation during the freeze-thaw process.…”
Section: Resultssupporting
confidence: 90%
“…Custom gDNA extraction workflows have been described, but many current methods are low in extraction yield, throughput and often not tested for NGS or microbiome purposes or optimized for soil (Abdel‐Latif & Osman, 2017; Zou et al, 2017). Commonly used protocols for nucleic acid purification are often column and centrifuge based, which are more laborious, harder to automate and so not easily used in a high‐throughput manner or scaled economically (Hamedi et al, 2016; Miao et al, 2014; Narayan et al, 2016; Oberacker et al, 2019). More recent open‐source protocols for rapid DNA purification using coated magnetic particles (Oberacker et al, 2019) or even cellulose (Zou et al, 2017) address many of these shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, some other compounds such as lignin are also exist in the cell wall structure (Somerville et al, 2004). Lignin removal is one of the major challenges in the procedure of DNA extraction from plant or environmental samples (Hamedi et al, 2021). In archaea, the cell wall is mainly composed of pseudo-peptidoglycan, S-layer, or polysaccharides.…”
Section: Cell Wallmentioning
confidence: 99%
“…These lysis approaches require more powerful tools to achieve cell disruption and subsequently extraction of DNA. In these circumstances, a combination of the lysis methods are used (Hamedi et al, 2021). Common examples of this approach are metagenomic studies of soil (Nesme et al, 2016), plant roots (Soni et al, 2017), mammalians gut (Maccaferri et al, 2011), and feces (Srivathsan et al, 2016).…”
Section: Cell Lysis In the Surrounding Environmentmentioning
confidence: 99%